INNOVATIVE DIRECTIONS OF INCREASING THE TOURISM CAPACITY OF NAVAI REGION - Turayev Abduvohid,Toshpulatov Firdavs Khusniddinovich (Ethiopian International Journal of Multidisciplinary Research, 2026)
This article studies innovative directions for increasing the tourism potential of Navoi region based on scientific analysis. The possibilities of tourism development based on the natural, historical and economic resources of the region are assessed. The main trends in the development of regional tourism in recent years are analyzed based on regulatory and legal documents aimed at developing the tourism sector in the Republic of Uzbekistan and official statistical data.